The presence of aflatoxins and ochratoxin A in rice and rice products; and evaluation of dietary intake. (1st November 2016) - Iqbal, Shahzad Zafar; Asi, Muhammad Rafique; Hanif, Usman; Zuber, Muhammad; Jinap, S.
Highlights: About 35% of the samples were positive with AFs contamination. Samples 19% and 24% were found to be above the EU limits for AFB1 and total AFs. The highest mean level of AFB1 & total AFs were found in brown rice samples i.e. 8.91 and 12.4 μg/kg. Almost 19% samples were found contaminated with OTA. About 15% samples were found to be above the EU maximum content for OTA. Abstract: In present study aflatoxins (AFs) and ochratoxin A (OTA) were analysed in 208 samples of rice and products collected from central areas of Punjab, Pakistan. The analysis was carried out using HPLC equipped with fluorescence detector. The results have shown that 35% of the samples were found contaminated with AFs, out of which 19% and 24% samples were found to be above the European Union (EU) maximum content for AFB1 and total AFs, respectively. About 19% samples were found contaminated with OTA and 14% samples were found to be above the EU maximum content. The highest mean level of AFB1 and total AFs were found in brown rice samples i.e. 8.91 and 12.4 μg/kg, respectively. However, white rice samples have shown the highest mean level of OTA (8.50 μg/kg) with highest level of 24.9 μg/kg. The high mean dietary exposure 22.2 and 24.2 ng kg −1  bw day −1 to AFB1 and OTA, respectively poses significant health hazard for local population.